2022
DOI: 10.1038/s41746-021-00548-8
|View full text |Cite
|
Sign up to set email alerts
|

Digital health tools for the passive monitoring of depression: a systematic review of methods

Abstract: The use of digital tools to measure physiological and behavioural variables of potential relevance to mental health is a growing field sitting at the intersection between computer science, engineering, and clinical science. We summarised the literature on remote measuring technologies, mapping methodological challenges and threats to reproducibility, and identified leading digital signals for depression. Medical and computer science databases were searched between January 2007 and November 2019. Published stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
99
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 91 publications
7
99
0
Order By: Relevance
“…In the interest of open and reproducible science, we will follow basic transparency recommendations,13 47–49 including the reporting of basic demographic and clinical data, attrition and participation rates, missing data, evidence of the validity or reliability of the sensors and devices used. For each behavioural feature, a full definition and description of feature construction will be provided, with links to GitHub repositories and source code, where available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the interest of open and reproducible science, we will follow basic transparency recommendations,13 47–49 including the reporting of basic demographic and clinical data, attrition and participation rates, missing data, evidence of the validity or reliability of the sensors and devices used. For each behavioural feature, a full definition and description of feature construction will be provided, with links to GitHub repositories and source code, where available.…”
Section: Discussionmentioning
confidence: 99%
“…Given the relative recency of the field, and with an eye towards clinical implementation, studies on RMTs and depression have largely comprised proof-of-concept, feasibility and acceptability studies. While studies show RMTs to be generally feasible and acceptable,12 the data predominantly come from small, non-clinical or student samples with a median follow-up time of 2 weeks 13…”
Section: Introductionmentioning
confidence: 99%
“…It has also often used very small sample sizes and/or short monitoring periods [15,17,21,22]. Recent reviews of this emerging literature have highlighted gaps in reporting on participant exclusions, attrition, and compliance that are necessary to assess selection biases and feasibility of these more novel personal sensing methods [36][37][38].…”
Section: Personal Sensingmentioning
confidence: 99%
“…Except for a slight difference in accelerometer between Black and White participants, the researchers did not find significant differences in missingness across race, gender, or education background 8 , but they did report a difference in GPS data coverage between Android and iOS users. Another large study with 623 participants using the RADAR platform examining data collected from November 2017-June 2020 found that only 110 participants had >50% data across all data types collected 10 . In addition, the researchers found no link between baseline depression and data availability in their sample, which suggests digital phenotyping methods are applicable regardless of illness severity.…”
Section: Introductionmentioning
confidence: 99%